THE WORLD OF SIMULACRA AND ROMANTICS IN THE DI KAKI BUKIT CIBALAK- A NOVEL WRITTEN BY AHMAD TOHARI - Harijanti, Sutji; Nuryatin, Agus; Rustono,; Doyin, Muh (International Journal of Psychosocial Rehabilitation, 2020)
Hyperreality is a tool of the world of simulakra. This tool is used by the author of the novel In the Bukit Cibalak to invite the reader toward real events that actually happened. One of the nature of literature is fictional. Through the creation of excess fiction, the storyline becomes as real as possible. On the contrary, between the real and the desired (the ideal) needs to be fought for to make it happen. Therefore, the idea or ideology of the text becomes a tool (tool) as well as an ideological site of various interests. The problem studied first needs to be seen from the structure of the text from an ideological point of view in order to find a worldview model of the text. The second problem is how the romantic worldview and the world of simulacra in the text. Through Goldmann's dialectical method, it was found that the structure of the text was built through pairs of opposition between rural-urban, male-female, poor-rich, real and ideal. Romantic worldview, which is the union between the real and the ideal can be realized through the character Pambudi as an agent. The world of simulacra is an interesting tool as a media for ideas such as intermingling in interethnic marriages.